Decision making in organizations - Roberto, Michael A. (Henry Stewart Talks, 2011)
Decision-making blunders, Decision-making myths, Multiple levels of analysis, Cognitive biases, Framing, Team design, Psychological safety, Organizational structure, Organizational culture, Leadership